Gulf Arab E‐Business Environment: Localization Strategy Insights. (22nd September 2015) - Benmamoun, Mamoun; Sobh, Rana; Singh, Nitish; Moura, Francisco Tigre
Abstract : The Gulf Arab region, particularly Qatar and the United Arab Emirates (UAE), took significant steps toward adopting e‐business and is poised to become a significant online marketplace. The region has a number of vital ingredients that could make it an e‐commerce powerhouse; however, e‐commerce has not reached its full potential. In this article, the authors explore the e‐business environment in the Gulf Arab region and shed light on some of the opportunities and challenges that are shaping and restricting e‐business infiltration. The article places greater emphasis on the idea of localization and how it may impact consumer behavior and expansion of e‐commerce. We argue that by increasing the focus on culturally customized online content by considering country‐level cultural, geopolitical, and linguistic factors, this region could be lucrative for companies looking to attract online consumers. © 2015 Wiley Periodicals, Inc.